1999
DOI: 10.1074/jbc.274.12.8299
|View full text |Cite
|
Sign up to set email alerts
|

A Novel MDMX Transcript Expressed in a Variety of Transformed Cell Lines Encodes a Truncated Protein with Potent p53 Repressive Activity

Abstract: The MDMX gene product is related to the MDM2 oncoprotein, both of which interact with the p53 tumor suppressor. We have identified a novel transcript of the MDMX gene that is expressed in a variety of cell lines, and in particular, in growing and transformed cells. This transcript is identical to the published sequence yet it has a short internal deletion of 68 base pairs. This deletion produces a shift in the reading frame after codon 114, resulting in the inclusion of a stop codon at amino acid residue 127 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
113
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 99 publications
(122 citation statements)
references
References 34 publications
9
113
0
Order By: Relevance
“…The calculated weight of the HDMX-S protein is 15 kDa, and the difference compared to the apparent weight observed after Western analysis suggests that HDMX-S undergoes posttranslational modification. 12 In our analysis, HDMX-S protein could be detected in cell lysates isolated from the samples that also showed elevated HDMX-S/FL-HDMX mRNA ratios. The band intensities have been analyzed by means of densitometry and were normalized against the actin expression levels within the same sample.…”
Section: Hdmx-s and Fl-hdmx Protein Expressionsupporting
confidence: 48%
See 4 more Smart Citations
“…The calculated weight of the HDMX-S protein is 15 kDa, and the difference compared to the apparent weight observed after Western analysis suggests that HDMX-S undergoes posttranslational modification. 12 In our analysis, HDMX-S protein could be detected in cell lysates isolated from the samples that also showed elevated HDMX-S/FL-HDMX mRNA ratios. The band intensities have been analyzed by means of densitometry and were normalized against the actin expression levels within the same sample.…”
Section: Hdmx-s and Fl-hdmx Protein Expressionsupporting
confidence: 48%
“…However, this association was not observed in anaplastic gliomas and low-grade gliomas. 8 Studies of Rallapalli et al 12 and de Graaf et al 13 revealed that the truncated proteins encoded by both MDMX-S and HDMX-S are more efficient at suppressing p53-mediated transactivation and induction of apoptosis than FL-MDMX or FL-HDMX, respectively. It is therefore conceivable that the upregulation of HDMX-S might contribute to the neoplastic transformation of cells by inactivating wt-p53.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations